Flexible flexible ensemble docking protocol for screening HIV-1 protease inhibitors - Muñoz, Ewell Gabriel A.; Belleza, Isabella Marie N.; Dela cruz, Dianne Salve O.; Padilla, Vince Lambert H. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Despite significant advances in computational chemistry, incorporation of protein flexibility remains to be a challenge. Recent approaches to predict binding pose with flexible receptors is limited by its computationally expensive models. Hence, it is important to find new methods to treat protein models as flexible bodies that use less computing power. In this work, we have developed a quick and novel docking protocol that accounts for protein flexibility which is less computationally expensive. Diferent structures were generated using short-range molecular dynamics through GROMACS 2023 where top ranking clusters were used for docking a ligand set. Residues with degrees of torsional flexibility were assigned in AutoDock Tools 1.5.6 to allow full flexibility of the ensemble during docking. The docking protocol was validated using HIV-1 protease inhibitors containing 12 active inhibitors, 7 inactives, and 480 decoys in terms of binding mode and energy score predictions. A success rate (SR) of 91.7% was obtained with the criteria of RMSD < 2.0 in the cluster group with the best binding energy. In contrast to standard protocols such as single receptor docking (16.7 -75.0%), flexible docking (75.0%), and ensemble docking (75.0%), this SR is higher. The protocol was further assessed by its ability to discriminate binders from non-binders, which demonstrated that incorporating protein flexibility using ensembles and flexible torsions (ASP25, ASP25", and THR80') still resulted in an excellent discriminating ability at AUROC = 0.99. This novel protocol may provide an improvement over existing strategies or future attempts to incorporate protein flexibility in molecular docking.
Thesis (Bachelor of Science in Pharmaceutical Sciences)--University of the Philippines Manila, June 2023
Keywords: HIV (Viruses)--Philippines.